Work-life balance policies: adjusting them into everyday life (Cadernos de Psicologia Social do Trabalho, 2008)
Starting with a social-construction-of-technology (SCOT) approach and a gender perspective, we have considered to show the relation that exists between the user, in this case, the Professors and the work-life balance policies, that Universitat Autònoma of Barcelona offers, in Bellaterra. We will see the translation strategies of these instruments of conciliation, that are reflected across the way in which the domestication processes are completed. We will discover that the technologies capacities are never given per se, but to hold its uses always goes through a work of interpretation; translation that in this case is related to a sexist and hierarchic organizational culture.